(untitled) (INNOVATIVE ECONOMY, 2025)
Voloshchuk K.B., Popovych K.-D.М. KEY STRATEGIC DIRECTIONS OF RESEARCH AND INNOVATION AND REGULATION OF CONTRACTUAL RELATIONS IN THE PROCESS OF DEEPENING TRADE AND ECONOMIC INTEGRATION OF UKRAINE AND THE EUROPEAN UNION Purpose. The aim of the article is to identify and summarize the substantive priorities for the formation of strategic directions of research and innovation, to regulate contractual relations in the context of deepening trade and economic integration of Ukraine with the European Union. Methodology of research. In the process of research, general scientific and special methods were used. In particular, the method of cause-and-effect analysis made it possible to identify the sources of the formation of strategic approaches in the context of changes taking place in modern conditions. The method of structural and logical analysis made it possible to clarify the substantive directions of global cooperation, as well as to characterize the features of the differentiation of approaches to the regulation of contractual relations in the context of deepening trade and economic integration of Ukraine with the European Union. The following methods were used among the general scientific: analytical – to assess the development of science, technology and innovation in Ukraine and the European Union countries, statistical methods, conjunctural analysis – to identify signs of asymmetry due to the predominance of the raw material component in Ukrainian exports, economic modelling – to identify the gap in gross national income per capita between Ukraine and the EU countries and the direct impact on reducing EU spending within the framework of the implementation of cohesion policy, generalization – to identify specific categories of goods, the production of which in Ukraine can replace part of imports on EU markets, analogies – to specify SMART goals for the development of research and innovation in the context of Ukraine’s European integration, synthesis – to assess new opportunities for localizing production in Ukraine and attracting investments under European standards in research and innovation for the recovery of the economy and a hypothetical approach to new formats of cooperation, friendshoring, and nirshoring. Findings. An innovative model of EU economic growth in the context of geopolitical tension was formed, which involves reducing dependence on third countries, activating friendshoring and building up internal production and technological potential. In this context, the role of Ukraine as a strategic partner in the supply of critically important raw materials, food and the development of industrial cooperation was defined. It was established that the integration of Ukraine into the European scientific and innovative space requires a systemic approach based on the principles of open strategic autonomy of the EU through joint development and implementation of policies covering critical sectors - in particular energy, digital technologies, defence industry, food security and sustainable development. The need to develop mechanisms for contractual relations was proven, taking into account new formats of cooperation, friendshoring, nirshoring, the creation of joint ventures, industrial alliances and integrated value chains, new opportunities for localization of production in Ukraine and attracting investments under European standards in research and innovation for economic recovery. Originality. The formation of key strategic priorities for research and innovation in order to strengthen the European and expand the Ukrainian research space by coordinating initiatives at various levels on the basis of regulating stable and predictable contractual relations with the determining factor of mutual trust in the business environment and the equivalence of Ukrainian-European partners in the context of deepening trade and economic integration of Ukraine with the European Union has been further developed. Practical value. The results of the conducted research can become a scientific basis for the development of mechanisms of contractual relations in the process of deepening the trade and economic integration of Ukraine with the EU, and the implementation of practical recommendations will make it possible to significantly reduce the gap in GDP per capita in Ukraine and EU countries. Key words: Ukraine, Europe, strategic directions, research, innovation, regulation, contractual relations, trade, economy, integration.